Peradapan Islam Pada Masa Abu Bakar Ash-Shiddiq - Fifi Sumanti; Refiana Nurlita Sari; Hendi Pratama; M. Solihin; Eka Talita Anggraeni; Gita Ramadhana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This article discusses the caliph Abu Bakr ash Siddiq as the first caliph of Muslims after the death of the Prophet Muhammad. Before being led by the Caliph, Muslims were led by an Apostle, the messenger of Allah, named Prophet Muhammad SAW. Before the prophet was born in Arabia had diverse beliefs and could be said to be the Age of Jahiliyah. After the Prophet Muhammad was born again, the life of the Arab occupation began to change according to the teachings of the Qur'an. After the death of the new prophet Muhammad called the leadership period of the Khulafa ar Rasyidun period, where the first khalifa named Abu Bakr Ash Siddiq who was born in 573 AD and died on 23 Jumadil Akhir 13H/634M. he was a friend of the prophet, during his reign many Arabs returned to their previous religion (apostasy) and many who claimed to be prophets did not pay zakat. caliph Abu Bakr Ash Shiddiq consulted with the leaders of the Muhajirin and Ansar about their departure to the north. At the time of the ashes, education was also very important. This article uses historical (historical) research methods to search, collect, prove, interpret, and present the results of an imaginative reconstruction of the past according to its traces.